Diabetes Self-Management and Self-Efficacy Training for Diabetes Mellitus Patients - Arbani Batubara; Agustina Boru Gultom; Dedy Fernandes (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT This community service program aimed to improve self-efficacy and reduce stress in diabetes mellitus patients. The training was held on April 28 and 29, 2026, involving 30 diabetes mellitus patients from two villages in the working area of the Sei Semayang Community Health Center, Deli Serdang Regency, each with 15 participants from Sei Semayang Village and Serba Jadi Village. The approach used was the Participatory Action Research (PAR) method, this activity included a pre-test measuring self-efficacy and stress using a questionnaire, a discussion on the description of diabetes mellitus, a discussion accompanied by demonstrations and redemonstrations regarding diabetes mellitus self-management, and diabetes mellitus self-efficacy, with the help of a booklet, and a post-test with the same measurements and questionnaires. The results of community service activities show a positive impact on the self-efficacy of diabetes mellitus patients increasing from a score of 48.33 to a score of 55.23, on stress decreasing from a score of 36.00 to a score of 22.00 and based on the Wilcoxon test showing significant results with a p value of 0.0001 each. This increase indicates that the training effectively increases self-efficacy and reduces stress in diabetes mellitus patients to be able to manage daily life regarding diet, physical activity, foot care and foot exercises, control their own blood glucose, stress management and manage their self-efficacy. This activity contributes to strengthening the attitudes and emotions of participants to be able to improve their quality of life in living their daily lives. Keywords: Diabetes Self-Management and Self-Efficacy Training, Self-Efficacy, Stress, Diabetes Mellitus.